Acute Diarrhea In Children With Moderate To Severe Dehydration: A Literature Review - Usman, Disman; Mulya , Nadia; Patiwael , Astriani; Sari , Ayu Yuliana; anisa , anisa; Zamrina , Waode; Ramadani , Suci; Fahril , Fahril; Purnamasari , Anisa (PT. Nursing Genius Care, 2025)
Background: Acute diarrhea is a medical condition with the second highest mortality rate after pneumonia. It is characterized by more than 14 days of frequent bowel movements with watery stools, leading to dehydration and the risk of electrolyte imbalance, often caused by Escherichia coli (E. coli) infection. Purpose: To explore therapeutic interventions for acute diarrhea in children with moderate and severe dehydration. Methods: A systematic literature search was conducted across multiple databases, including ScienceDirect, PubMed, and Google Scholar, using Boolean terms and specific filters to identify relevant articles. The inclusion criteria were full-text articles published between 2022 to 2025. Results: A total of 10 articles met the predefined keywords and selection criteria. Conclusion: Although rotavirus vaccination has proven to be effective, the selection and adaptation of vaccination strategies must be tailored to local conditions to achieve optimal outcomes in children with acute diarrhea accompanied by moderate to severe dehydration.